Awareness and Disposal Practices of Medicines among the Community in Hawassa City, Ethiopia - Daniel Woldamicael Bekele; Elias Dadebo; Girma Tilahun; Zinabu Gebremariam (Journal of Toxicology)
Despite the enormous benefits medicines provide to humanity, their improper disposal frequently leads to detrimental consequences on the environment. Lack of awareness and malpractices concerning expired, leftover, or unused (ELU) medicines have become concerns worldwide. This study assessed community awareness and practices regarding the disposal of ELU medicines in Hawassa City, Ethiopia. A community-based descriptive cross-sectional survey design was used among the urban population of Hawassa City. Multistage sampling procedures were employed to select 405 household (HH) respondents, and purposive sampling techniques were used to select key experts (KEs) and key informants (KIs). A pretested questionnaire was designed for HHs, KEs, and KIs. The results of the study showed that analgesics and antibiotics, used in 52 and 27% of the HHs, respectively, were the most commonly consumed medicines in this city. The vast majority (95.5%) of the HHs did not store expired medicines but disposed of them. Only 10% of the HHs were well informed on how to dispose of ELU medicines. Most (70%) KEs and KIs revealed that there were no awareness-creation mechanisms for the safe disposal of ELU medicines. A significantly high p < 0.05 percentage (76%) of the HH respondents who were well informed on how to dispose of ELU medicines had higher education, but most (95%) of them indicated that they would not be willing to be involved in “ELU-take-back” programs even if there had been such a mechanism. Field observations confirm significant amounts of medical waste improperly discarded in various areas, including the shores of Lake Hawassa near Hawassa City. The study has shown that awareness of the management of ELU medicines is critically lacking in the community of Hawassa City, posing environmental and human health risks. Moreover, the majority of households practice unsafe disposal of ELU medicines, leading to human health threats and environmental risk.